Tratamento da água residuária da indústria de gelatina pelo processo de lodos ativados - Albano, Jussara Cristina de Almeida (1997)
Gelatin is a colloidal protein of great importance in food, pharmaceutical, and photography industry because of its adhesive, protective, and coagulative properties. Gelatin is obtained by the partial hydrolysis of collagen, the chief protein component in skins, bones, and white connective tissues of the animal body. The process of collagen extraction generates a reasonable volume of wastewater highly polluter that besides the high organic load and has greasy material and sulphide in reasonable concentrations. In this work, the treatment of this wastewater in the Activated Sludge Process was studied. The equip ment used was constituted by a 10L reactor, aerate and mechanically agitate. The start-up of process was carried out after inoculation with aerobic sludge, from sewer treatment plant of Londrina- PR, previously acclimated to wastewater. The study was made to obtain the Best hydraulic retention time (HRT) for the system. The HRT used were 24, 12, and 18 h. The parameters of control were COD, MLVSS, sulphide, greasy material, dehydrogenase activity , dissolved oxygen, and turbidity. The results obtained shown efficient performance in the experiment 1, with TRH 24 h, with COD and sulphide reduction of 91 and 86%, respectively. The experiment 2 obtained low efficiency, reaching average removal efficiency of 47 and 70% to COD and sulphide, respectively. In the experiment 3 the results were analogous to experiment 1 for these parameters. The experiment 2, with high input concentration of grease material, showed lower level of output turbidity than the experiment 3, with low input concentration of grease material. This is probably due the presence of filamentous organisms. The results obtained permit to conclude that the best HRT for the system is between 12 and 18h, and high concentration of grease material can be favourable to development of filamentous organisms in the reactor.